PERLINDUNGAN PEREMPUAN DAN ANAK KETIKA PERANG DALAM HUKUM HUMANITER INTERNASIONAL - Triana, Nita (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2009)
War always takes victims, and the worst victims are civilians (women and children). International Humanitarian Lawregulates to protect civilians (Women and children) on the war. The important principle of The Humanitarian Law is a Distinction Principle. Aprinciple that distinct population in a country which is being hostilities, Combatant and Civilians. Combatant is a member ofArmed Group so ithas direct relationship with hostilities. Whereas civilians is a population out of Armed Group who have to be protected. If InternationalHumanitarian Law is attacted, so UNO (PBB) with its instrument is a Security Council (Dewan Keamanan) to give sanctions by givingresolution, and in a juridicaly the Country have to follow this resolution without requisite